VIEWING LIFE THROUGH DEATH'S PERSPECTIVE: The Confluence of The Theravada Buddhism's Theology of Death with the Christian Faith - Kurniawan, Markus; Prihantoro, Yogi (Sekolah Tinggi Teologi Widya Agape dan Perkumpulan Teolog Agama Kristen Indonesia, 2023)
Death is a very close thing in human life, even a certain thing. It is impossible to predict when this death will occur. Therefore, death is also part of a mysterious phenomenon that occurs repeatedly with the same subject, namely people. The saying that the closest friend is dead. Sooner or later, willingly, or not, every human being will experience death that no one can avoid. When it comes to reacting to death, some people are afraid, some are worried, and some sincerely accept it. This article uses descriptive – analysis using Zur Theologie des Todes – ‘On the Theology of Death,’ published in 1958. Karl Rahner developed his theological approach to death. Death, according to Rahner, is an event that affects the whole human being, not just the body, while the immortal soul remains fundamentally intact. According to the Buddhist concept, death is the end of suffering. Birth, dissatisfaction, pain, and dissatisfaction, are suffering in life. So, death is a possible way to reduce pain Death, which is seen as the end of one's life, should be seen as an act in itself. Rahner interprets fulfillment as belonging to death itself. Nonetheless, Rahner's theory, like Augustine's, continues to evolve, and his treatment of the